In-depth proteomic characterization of Schistosoma haematobium: Towards the development of new tools for elimination - Sotillo, Javier; Pearson, Mark S.; Becker, Luke; Mekonnen, Gebeyaw G.; Amoah, Abena S.; van Dam, Govert; Corstjens, Paul L. A. M.; Murray, Janice; Mduluza, Takafira; Mutapi, Francisca; Loukas, Alex (PLOS Neglected Tropical Diseases, 2019)
Author summary Schistosomiasis is a neglected tropical disease affecting millions of people worldwide. Of the main three species affecting humans, Schistosoma haematobium is the most common, and is the leading cause of urogenital schistosomiasis. This parasite can cause a range of clinical complications associated with bladder pathogenesis, including squamous cell carcinoma as well as genital malignancy in women. Herein, we have performed the first comprehensive characterisation of the proteins implicated in host-parasite interactions (secreted and surface proteins from the adult flukes and secreted and soluble egg proteins) in order to advance our understanding of the parasite’s biology. Furthermore, we have characterised the different antibody responses in urine from infected human subjects from an endemic area presenting different infection intensities. The data obtained in this study can be used as a first step towards the development of novel tools for the control of urogenital schistosomiasis.